2009
DOI: 10.1590/s0066-782x2009000700009
|View full text |Cite
|
Sign up to set email alerts
|

Medindo a pressão arterial em exercício aeróbico: subsídios para reabilitação cardíaca

Abstract: SummaryBackground: Institutional documents recommend that hemodynamic variables -heart rate (HR) and systolic (SAP) and diastolic arterial pressure (DAP) -be routinely controlled at the aerobic part of supervised exercise sessions for coronary disease patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 18 publications
0
5
0
1
Order By: Relevance
“…That might be due to the fact that, during the exercise, the patients were no longer using the positive pressure 23 . However, at the assessment of the double-product at the end of the exercise, lower values of this physiological parameter were observed in the group of patients submitted to NIVS.…”
Section: Discussionmentioning
confidence: 99%
“…That might be due to the fact that, during the exercise, the patients were no longer using the positive pressure 23 . However, at the assessment of the double-product at the end of the exercise, lower values of this physiological parameter were observed in the group of patients submitted to NIVS.…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate any possibility of interference by the examiner on any differences or changes in hemodynamic variables, HR, SBP and DBP measurements were obtained using a digital Tango+ sphygmomanometer by the oscillometric method (Suntech, United States), using the detection of the RR interval of the electrocardiogram as reference, thus minimizing the influence of any noise or artifacts of the exercise, a basal value of 180 mmHg of inflation and a deflation rate of 5 This equipment is properly certified for blood pressure measurements, according to the technical standards of the country of manufacture, and has been used in other clinical studies [27][28][29] . Using the device's manual mode, measurements were made at rest, prior to determining the maximal handgrip strength, starting the inflation of the cuff at 20 and 80 seconds of the two maneuvers made with the left arm and also 1 minute after completion of the last maneuver.…”
Section: Protocolmentioning
confidence: 99%
“…The circulatory response to a 50-meter walk in acute coronary syndrome was presented by Dias et al3 Furtado et al reported on blood pressure measurements during aerobic exercise in cardiac rehabilitation,4 whereas Oliveira et al reported on the effect of the walk test on the length of hospital stay for cardiac surgery patients 5. The relationships between fitness, waist circumference and hypertension in elderly Brazilian women were investigated by Krause et al6 Pelegrino et al studied the influence of lean body mass on cardiopulmonary repercussions during the six-minute walk test in patients with chronic obstructive pulmonary disease (COPD) 7…”
Section: Methodsmentioning
confidence: 99%